Pengaruh Pembelajaran Penemuan Terbimbing Terhadap Kemampuan Pemecahan Masalah Matematika Siswa - Ramadhani Ramadhani (Universitas Muslim Nusantara Al Washliyah, 2018)
The researchis quasi experiment research. The researsch aims to determine the effect of guided discovery learning method to mathematical problem solving ability. Population in this study were SMP Swasta 2 TAMORA, and the sampel is IX-1 class students. The instrument in the research is the test of mathematical probling solving ability. The result of the research were analyzed by correlation test is 0,701. And thitung 4,610 > ttabel 2,07, so there is the significant influence between guided discovery learning on students’ mathematical problem solving ability. Keywords : Guided Discovery Learning, Mathematical Problem Solving Ability